PENGARUH HUBUNGAN PEMASARAN, KUALITAS LAYANAN TERHADAP LOYALITAS DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING - Krisdayanti, Helisia; Panorama, Maya; Azwari, Peny Cahaya (Islamic Economics Program, Faculty of Islamic Economics and Business, 2020)
Abstract Gojek is a company that offers taxi transportation services that are integrated with technology, using the motorcycle taxi booking application. However, the problem now is the large number of motorcycle taxi driver, causing intense competition, not only in one company but in other transportation companies. There is a rates war (promotion) given by other companies that causes the entry and exit of the driver's and causes some rogue drivers to play two legs. Uncontrolled driver, such as: driver use vehicles that are incompatible with those recorded in the application. And not provided a place to